Study on Key Technology of WLAN Service Non-Sense Authentication Method - Linjiang Li (Dianxin kexue)
WLAN service non-sense authentication is one kind of automatic identification access authentication method, which can provide users with convenient WLAN access service, change the traditional cumbersome access ways, enhance the user perception. The current situation and the problems in access authentication of WLAN service were introduced, the IEEE 802.1x architecture and authentication method were analyzed, the key technology of non-sense authentication based on the EAP for principle,network structure and the certification process were discussed, and the main non-sense authentication method were compared.Finally,its application promotion were summarized.